Systematization and Description of the Arterial Blood Supply of the Paleopallia areas in the Brain Surface of the Wild Boar (Sus scrofa scrofa) - de Nascimento, Patrícia Bastos; Dias Oliveira, João César; Campos, Rui (Acta Scientiae Veterinariae, 2019)
Background: The study was performed on wild boar (Sus scrofa scrofa) wich is a wild ancestor of the domestic pig and is not part of Brazilian fauna. The arterial blood supply of the encephalus has been studied by some researchers, who have systematized the cerebral blood supply from the rostral and caudal epidural rete mirabile and its sources in wild boar until the blood supply of the base of the brain. The objective was to improve the understanding of the arterial blood supply of the brain, particularly the paleopallium, of the wild boar and to provide a reference for comparative anatomy studies. Materials, Methods & Results: A total of 30 brains were obtained from an officially authorised slaughterhouse and approved by Brazilian Institute of Environment and Natural Renowable Resources. The animals were desensitized, followed by bleending of the jugular veins and common carotid arteries near the entrance of the thorax, according to the slaughter procedure. Finally, the animals were decapitated at the level of axis vertebra. The cerebral arterial system of each animal was rinsed (cooled saline containing 2500 IU of heparin) and drained by the jugular veins, and vessels were filled with latex 603 stained with specific red dye. The heads were submerged for one hour in running water immersed in 20% formaldehyde for fixation; the brains were removed along with a cervical segment of the spinal cord. The duramater was removed, and the arteries were dissected. Schematic drawings of the ventral view of the all preparations were made using magnifying glasses and photographic records. The Nomina Anatomica Veterinaria was used to named the cerebral arteries and their branches, and calculation of pecentages was applied in the statistical analysis. The cerebral carotid artery originating from the rostral epidural rete mirabile emitted a rostral branch and a caudal branch on the side of the hypophysis gland. The rostral branch emitted one to three middle cerebral arteries and continued as rostral cerebral artery. The latter emitted the superficial and perforating central arteries, lateral rhinal artery, ethmoidal artery, medial branch and medial rhinal artery. Discussion: Wild boar is a macrosmatic animal, it presents well-developed areas of the paleopallium that are exclusively olfactory. Its extensive paleopallium was nourished by branches of the rostral cerebral artery and its collateral branches, including the lateral rhinal, ethmoidal, and medial branch and the medial rhinal artery. The rostral cerebral arteries and their collateral branches supplied blood to the olfactory bulb, olfactory peduncle, two-thirds of the lateral olfactory tract, medial olfactory tract, and rostral two-thirds of the olfactory trigone. The medial cerebral arteries within the lateral fossa of the brain, emitted superficial rostral central branches to the paleopallium, perforating central branches (striated) to the lateral fossa of the brain and caudal third of the olfactory trigone and caudal central branches to the piriform lobe. The rostral most two-thirds of a small medial band of the piriform lobe was vascularised by central branches originating mainly from the rostral branch of the cerebral cartotid artery. The paleopallium in the wild boar was nourished by branches of the cerebral rostral, middle and caudal arteries and by the central branches of the cerebral carotid artery. The arterial blood supply of the paleopallium in the wild boar was compared to the chinchilla, nutria, rabbit and pampas fox. Three cerebral vessels were mainly responsable for the emission of the central branches that supplied blood to the paleopallium, namely the middle, rostral, and caudal cerebral arteries. The differences or variations among these species were due to the type of cerebral blood supply in the formation of the cerebral arterial circle. Keywords : anatomy, brain, paleopallia, arteries, Artiodactila, wild boar.